SEROLOGICAL DIAGNOSIS (ROSE BENGAL) AND MOLECULAR (PCR) OF BRUCELLOSIS IN HUMAN - Cevallos Falquez, Orly Fernando (2010)
The objective of this research was: To determine the presence of brucellosis in the personnel working in the slaughterhouses of the cantons, Buena Fe, Quevedo, El Empalme and Pichincha, the serological test using Rose Bengal (RB) and molecular techniques ( PCR). Was used as a source of peripheral blood DNA and antibodies. Of a total of 115 blood samples collected at staff working in the slaughterhouses and slaughterers and operators, 54 (47%) and 15 (13%) were PCR positive and RB respectively, giving 61 (53%) and 100 (87%) negative for both tests accordingly. The average number of positive cases for the three populations except Pichincha by PCR was 3.4% and 39.4% RB. It takes care with the Pichincha Canton because 19 (70.3%) of samples were positive with RB of which 12 (44.4%) when analyzed with PCR were negative, and showed a 52.6% , indicating a high incidence of the disease. As long as the negative sample RB 8, 2 were PCR positive giving a correlation between negative 75%. The positive samples amplified a fragment of 725 pb. This work suggests that PCR is a highly efficient tool and very useful for diagnosis of brucellosis in humans.